1998
DOI: 10.1002/(sici)1096-9861(19980713)396:4<415::aid-cne1>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Early formation of sexually dimorphic glomeruli in the developing olfactory lobe of the brain of the mothManduca sexta

Abstract: The antennal lobes (ALs), the primary olfactory centers, of the moth Manduca sexta are sexually dimorphic. Only ALs of males possess the macroglomerular complex (MGC), the site of primary processing of information about the female's sex pheromone. To understand the development of identified, odor-specific olfactory glomeruli, we investigated the cellular events involved in the morphogenesis of the MGC by means of various fluorescence staining techniques and laser-scanning confocal microscopy. The MGC lies near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…In the one female investigated here, of H. virescens, two enlarged compartments were shown at the entrance of the antennal nerve, in a position corresponding to the male-specific MGC, the largest residing centrally at the antennal nerve entrance and a somewhat smaller unit in the dorsomedial position. Large female glomeruli have previously been described for the silk moth Bombyx mori (Koontz and Schneider, 1987) as well as for M. sexta (Ro ¨ssler et al, 1998). It has recently been reported that one of the two units identified in the latter mediates information specifically about the plant volatile linalool (King et al, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…In the one female investigated here, of H. virescens, two enlarged compartments were shown at the entrance of the antennal nerve, in a position corresponding to the male-specific MGC, the largest residing centrally at the antennal nerve entrance and a somewhat smaller unit in the dorsomedial position. Large female glomeruli have previously been described for the silk moth Bombyx mori (Koontz and Schneider, 1987) as well as for M. sexta (Ro ¨ssler et al, 1998). It has recently been reported that one of the two units identified in the latter mediates information specifically about the plant volatile linalool (King et al, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…1). In male Manduca , the MGC exists close to the entrance of the antennal nerve into the antennal lobe and comprises three glomeruli: the cumulus, the toroid-1, and the horseshoe-shaped toroid-2 (Heinbockel et al 1995; Homberg et al 1995; Rössler et al 1998). All three glomeruli of the MGC are targeted by axonal projections of olfactory receptor cells housed in the long trichoid sensilla in the antenna as revealed by specific anterograde labeling using cobalt lysine (Christensen et al 1995) or rhodamine dextrane staining techniques (Fig.…”
Section: Organization Of the Olfactory System In Male M Sextamentioning
confidence: 99%
“…Olfactory receptor cells in trichoid type-A sensilla project their axons mainly to two large, distinct, and sexually dimorphic glomeruli, the medial and lateral large female glomerulus (medLFG, latLFG) (Rössler et al 1998, 1999; Rospars and Hildebrand 2000). Other olfactory receptor cell afferents from these sensilla project to some of the 60 sexually isomorphic glomeruli in the antennal lobe (Shields and Hildebrand 2001a).…”
Section: Organization Of the Olfactory System In Female M Sextamentioning
confidence: 99%